Pengaruh Kualitas Produk, Citra Merek, Harga dan Lokasi Terhadap Keputusan Pembelian Cctv Zkteco - Saragih, Lenny Menara Sari; Parulian, Edison; Sudarso , Andriasan; Mailangkay, Yoseph Israel (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The purpose of this study was to determine the effect of product quality, brand image, price and location on the decision to buy CCTV ZKTeco.The method used in this research is descriptive quantitative method which is carried out through data collection using questionnaires and statistical test data analysis. The sample in this study were 80 consumers. The test instruments used are validity and reliability tests. Analysis of the data used is multiple linear regression analysis. The hypothesis test used is a partial t-test, simultaneous F-test and determination test. The results of the multiple linear regression test are Y = 2.109+ 0.046 X1 + 0.203 X2 - 0.144 X3 + 0.722X4 + e. The results showed that partially product quality affects purchasing decisions, brand image affects purchasing decisions, price has a negative effect on purchasing decisions and location affects purchasing decisions and simultaneously product quality, brand image, price and location affect ZKTeco CCTV purchasing decisions.